Efficacy and safety of prophylactic intraoperative sac embolization in EVAR for abdominal aortic aneurysm: A meta-analysis - Chen, Quan; Zhang, Yuan; Lei, Kangqing; Fu, Liangyin; Zhang, Dengxiao; Sun, Wanli; Shi, Chaohai; Niu, Qibing (Frontiers in Surgery, 2023)
Objective We aimed to investigate the effectiveness and safety of prophylactic sac embolization during endovascular aneurysm repair (EVAR) in patients suffering from abdominal aortic aneurysms. Methods We performed a systematic literature search of PubMed, Web of Science, EMbase, Cochrane Library, China National Knowledge Infrastructure (CNKI), VIP, Wanfang and China Biomedical Literature Database (CBM) to identify studies evaluating the outcomes of sac embolization vs. no embolization among patients who had received EVAR. The time limit of the search was from the establishing database to July 22, 2022. Outcome measures involved the type II endoleak rate, the other endoleak rate, the reintervention rate, mortality, and operation time. Fixed (no heterogeneity) or random effects models were constructed for each outcome. The outcomes are represented as the odds ratio (OR) with a 95% confidence interval (CI). Results Among the 2,622 studies screened, 13 studies involving 747 participants were included in the review. The incidence of early-term type II endoleak (OR = 0.2, 95% CI (0.13,0.31), P < 0.00001), mid-term type II endoleak (OR = 0.23, 95% CI (0.15,0.37), P < 0.00001), late-term type II endoleak (OR = 0.27, 95% CI (0.16,0.46), P < 0.00001) and reintervention (OR = 0.50, 95% CI (0.37,0.78), P = 0.002) within the sac embolization group were significantly lower than those in the non-embolization group. No significant differences were observed between the two groups were found for the other endoleak rates (OR = 0.67, 95% CI (0.34,1.32), P = 0.25), mortality (OR = 0.64, 95% CI (0.25,1.66), P = 0.36) and operation time operation (MD = 5.76, 95% CI (-8.30,19.83), P = 0.42). Conclusions EVAR combined with sac embolization effectively reduces the incidence of type II endoleak and the reintervention rate without enhancing the operation time. Therefore, more high-quality studies are still needed for validation due to the limited amount and quality of included literature. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42022365648.